Analisis Du pont System Sebagai Alat Ukur dalam Penilaian Kenerja Keuangan PT Inti Sari Perkasa Makassar - Burhanuddin Burhanuddin (Jurnal Publikasi Ilmu Manajemen, 2024)
This study aims to analyze and determine how financial performance using financial ratios based on the two pont system method for three periods from 2021 - 2023 and show the position of strengths and weaknesses of the factors that influence it. The object of this research is a distributor company of cooking ingredients and processed cakes, namely PT ISP. This research data, researchers took primary data with quantitative descriptive research type. Techniques in data collection are obtained from documentation studies of financial statements consisting of ROI, NPM, and TATO. The results of this study indicate that the financial performance of PT ISP cannot be said to be good because the resulting ROI percentage has decreased continuously. This decrease in ROI is influenced by the decreasing values of NPM and TATO. In addition, it is influenced by the amount of total assets compared to the net profit earned by the company.